Krisis Laut Merah : Implikasi Se Krisis Laut Merah : Implikasi Serangan Houthi terhadap Perdagangan Maritim dan Keamanan Global - Nandini, Nandini; Ma'arif, Syamsul; Syamsunasir, Syamsunasir; Widodo, Pujo (CV. AFDIFAL MAJU BERKAH, 2024)
The study explores the impact of the Houthi group's missile and drone attacks on Israeli commercial ships in the Red Sea, focusing on the broader implications for regional stability, maritime and global trade security. The strategic position of the Red Sea as an important trade route connecting the Middle East with Asia and Europe has made it an important area of international attention, especially after the Houthi attacks in November 2023. The research uses a qualitative approach, analysing data from a variety of sources including academic literature, official reports, and news articles. The findings highlight that the Houthi attacks have caused significant disruptions in maritime trade, with the capacity of container ships in the Red Sea decreasing by 80 percent as ships moved around Africa, resulting in higher costs and longer travel times. In addition, the attacks have exacerbated regional tensions and required increased military patrols by international forces. The study concludes that the ongoing Houthi aggression poses a serious threat not only to regional stability but also to global trade and security, and calls for coordinated international efforts to mitigate this impact.